Synthesis and characterization of orthopalladated complexes containing tridentate C, N, O-oxazolones. (1st August 2022) - Dalmau, David; Jiménez, Ana I.; Urriolabeitia, Esteban P.
Graphical abstract: Oxazolones as C, N, O-tridentate ligands have been prepared in two steps from Erlenmeyer-Plöchl method followed by acid deprotection. Further reactivity with Pd(OAc)2 takes place through CH and OH activation to give [Pd(C, N, O-oxazolone)(L)] complexes, where the Pd atom is located in a rigid environment. Highlights: New ( Z )-4-arylidene-2-( o -hydroxyphenyl)-5(4 H )-oxazolones have been prepared. These oxazolones can be C, N, O-orthopalladated to give mononuclear complexes. The oxazolones behave as strong C, N, O-tridentate ligands. The incorporation of the Pd to the oxazolone takes place through CH bond activation. Abstract: The ( Z )-4-aryliden-2-(2-acetoxyphenyl)-5(4 H )oxazolones 1a-1c react with H2 SO4 to give the corresponding ( Z )-4-aryliden-2-(2-hydroxyphenyl)-5(4 H )oxazolones 2a-2c .The molecular structures of 1c and 2a have been determined by X-ray diffraction methods, and show planar skeletons. Oxazolones 2a-2c are potential C, N, O-tridentate ligands towards transition metals, and their molecular design obeys to the search of a rigid environment around the metal. The reaction of Pd(OAc)2 with oxazolones 2a-2c (1:1 M ratio) in CF3 CO2 H or NCMe as solvents results in the synthesis of diverse complexes (3 –7 ). As a function of the reaction conditions, two different bonding modes have been characterized: N, O-chelate in the dinuclear complexes [Pd(κ 2 -N, O-2b, c )(μ -O2 CCF3 )]2 (3b, c ), as a result of the N -coordination and deprotonation of the hydroxy group; and C, N, O-tridentate in mononuclear complexes [Pd(κ 3 -C, N, O-2a, b )(L)] (L = CF3 CO2 H 4a, b ; dmso-d6 5a, b ; NCMe 6b ; pyridine 7b ), obtained after N -bonding, OH deprotonation and CH bond activation. All complexes have been fully characterized by HRMS and NMR methods, showing the high stability of the C, N, O-tridentate bonding mode.